Vibration characteristics analysis and structure optimization of air-pressure subsoiler. (January 2022) - Su, Hongjie; Cui, Hongmei; Li, Feiyu; Yideer, Chaolun; Zhu, Yaxiong; Ma, Zhipeng
Aiming at the problems of strong vibration, inconsistent subsoiling depth and high failure rate of air-pressure subsoiler, air-pressure subsoiler vibration characteristics was studied. In order to decrease the vibration, For the first time, the vibration characteristics of air-pressure subsoiler were obtained by modal analysis and vibration test. The vibration characteristics of the whole air-blown subsoiler are analyzed Through time domain analysis, it is found that the vibration acceleration of four deep loosening shovel is inconsistent. When the diesel engine is started, it is easy to cause inconsistent subsoiler depth. Then, by analyzing the vibration characteristics of the whole air-pressure subsoiler, it can be known that the external excitation source of the air-blown subsoiler is close to its own natural frequency. In order to avoid resonance caused by the vibration frequency of the external excitation source being close to the natural frequency of the air-pressure subsoiler, and to reduce the inconsistency of the subsoil depth, we optimize the design of air-pressure subsoiler. Instead of diesel engines, the steering gear box is connected with tractor power output shaft to provide power. The modal simulation of the optimized air-pressure subsoiler shows that the first-order natural frequency is obviously improved and the external excitation frequency is successfully avoided. It not only avoids resonance, reduces the damage of resonance components, but improves the service life of the subsoiler, greatly improves the structural reliability of the air-pressure subsoiler, at the same time, removes the main external excitation source, which greatly reduces the vibration in actual production and the inconsistency of subsoiling, which is of great significance in actual production. It provides a reference for the research of vibration characteristics, resonance avoidance and structure optimization of agricultural equipment.